Respuesta :

Answer:

see explanation

Step-by-step explanation:

Expand the factored form and compare coefficients of like terms with the original polynomial

a(x + 1)(x - 2)² + b(x + 2) + c

= a(x + 1)(x² - 4x + 4) + b(x + 2) + c

= a(x³ - 4x² + 4x + x² - 4x + 4) + b(x + 2) + c

= a(x³ - 3x² + 4) + b(x + 2) + c ← distribute parenthesis

= ax³ - 3ax² + 4a + bx + 2b + c

Compare x³ terms

ax³ with 2x³ , then a = 2

Compare x terms

bx = - 3x , then b = - 3

Compare constant terms

4a + 2b + c = 6

4(2) + 2(- 3) + c = 6

8 - 6 + c = 6

2 + c = 6 ( subtract 2 from both sides )

c = 4

Thus a = 2, b = - 3, c = 4